2015
DOI: 10.1037/neu0000176
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and neural correlates of facial versus nonfacial stimuli processing in adults with ADHD: An ERP study.

Abstract: The current results provide indication of modulation of face processing in adults with ADHD. ERP alterations, reflected in abnormally reduced P3 and N3 to face targets, may suggest ADHD-related abnormal recruitment of neural resources to process face stimuli. Behavioral and brain function measures of face processing may provide valuable additional tools for use in clinical assessment of ADHD in adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 73 publications
(112 reference statements)
3
21
2
Order By: Relevance
“…Thus, ADHD appeared to be associated with enhanced processing of angry faces despite the indication of enhanced attentional orienting to emotional stimuli in general. Another study using only angry faces did not find the same N170 effects, but instead showed that ADHD at age 24 was associated with enhanced target-P3b amplitude and reduced target-N3 amplitude (also known as LPN or late posterior negative slow wave) in response to angry faces, which was interpreted as an index of more effortful processing (Raz and Dan, 2015b) (Table 1A).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, ADHD appeared to be associated with enhanced processing of angry faces despite the indication of enhanced attentional orienting to emotional stimuli in general. Another study using only angry faces did not find the same N170 effects, but instead showed that ADHD at age 24 was associated with enhanced target-P3b amplitude and reduced target-N3 amplitude (also known as LPN or late posterior negative slow wave) in response to angry faces, which was interpreted as an index of more effortful processing (Raz and Dan, 2015b) (Table 1A).…”
Section: Resultsmentioning
confidence: 98%
“…Task paradigms that are broadly relevant to socioemotional processing might also combine parameters that have been considered separately in the ADHD and ASD literature. Face processing tasks could, for example, consider a range of positive and negative emotions, so to establish if processing of specific emotions are disorder-specific (e.g., Raz and Dan, 2015a, 2015b). Additional parameters to consider are passive viewing versus active recognition and faces versus non-faces, given the inconsistency, even in the ASD literature, in relation to atypical face processing (e.g., Faja et al, 2016; O’Connor et al, 2005; Stavropoulos et al, 2016; Webb et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, situational stimuli such as interactions and overall pictures were more easily interpreted by children with ADHD [27]. Also, in 2015, Raz and Dan showed that adults with ADHD had worse performance in recognition of facial expressions but were more proficient than controls in situational analysis [28]. However, none of the participants from the ADHD group were medicated during the study [28].…”
Section: Adhd the Perception Of Time And Time Processingmentioning
confidence: 99%
“…Also, in 2015, Raz and Dan showed that adults with ADHD had worse performance in recognition of facial expressions but were more proficient than controls in situational analysis [28]. However, none of the participants from the ADHD group were medicated during the study [28]. The influence of medications used in the treatment of ADHD, such as methylphenidate, was found to have a positive effect on the perception of time but, of interest, the same effect was found when monetary rewards were offered [29].…”
Section: Adhd the Perception Of Time And Time Processingmentioning
confidence: 99%
“…The oddball paradigm is also used to investigate the special role of emotional content in perception and attention 16 , by employing, for example, neutral facial expressions as the standard stimuli (i.e., "target") and emotional facial expressions as the deviant stimuli (i.e., "non-target"). Using such a paradigm, Raz and Dan 17 demonstrated that participants with ADHD generally perform worse than controls, as reflected in higher rates of omission errors and commission errors, slower RTs, and higher RTSD. However, higher rates of omissions and slower RTs in the ADHD participants compared with controls were only found in response to face targets but not in response to geometric shape targets, suggesting a specific ADHD-related deficit in the processing of emotional facial expressions.…”
Section: Introductionmentioning
confidence: 99%